PENGARUH PENAMBAHAN KARAGINAN TERHADAP MUTU PERMEN JELLY DARI BUAH PEDADA (Sonneratia caseolaris) - ', Afriyanto '; Ali, Akhyar '; ', Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of the study was to obtain the effect of the addition of carrageenanon the quality of jelly candy pedada fruit (Sonneratia caseolaris). The experiment research used a completely randomized design (CRD), which consists of four treatments and four replications. The treatments were KP1 (5%Addition of carrageenan:45% pedadajuice), KP2 (10%Addition of carrageenan:40% pedadajuice), KP3 (15%Addition of carrageenan:35% pedada juice), and KP4 (20%Addition of carrageenan:30% pedadajuice). Data were obtain using ANOVA and DNMRT at 5%. The result showed that the treatments has significantlyaffected on water content, reducing sugar content, color, flavor, and overall assessment. Meanwhile  on ash content, flavour, and texture the treatments did not significantly affected. The best treatment is KP4(20%Addition of carrageenan:30% pedadajuice) with a water content (18.71%), ash content (1.46%), levels of reducing sugars (12.32%). Moreover the sensory assesment showed that panelists  prefered the jelly candy.   Keywords: Jelly  Candy, pedada fruit juice, carrageenan